Stepwise Embryonic Toxicity of Silver Nanoparticles on Oryzias latipes. (30th July 2013) - Cho, Jae-Gu; Kim, Kyung-Tae; Ryu, Tae-Kwon; Lee, Jae-woo; Kim, Ji-Eun; Kim, Jungkon; Lee, Byoung-Cheun; Jo, Eun-Hye; Yoon, Junheon; Eom, Ig-chun; Choi, Kyunghee; Kim, Pilje
Abstract : The developmental toxicity of silver nanoparticles (AgNPs) was investigated following exposure of Oryzias latipes (medaka) embryos to 0.1−1 mg/L of homogeneously dispersed AgNPs for 14 days. During this period, developmental endpoints, including lethality, heart rate, and hatching rate, were evaluated by microscopy for different stages of medaka embryonic development. To compare toxic sensitivity, acute adult toxicity was assessed. There was no difference in acute lethal toxicity between embryo and adult medaka. Interestingly, we found that the increase in stepwise toxicity was dependent on the developmental stage of the embryo. Lethal embryonic toxicity increased from exposure days 1 to 3 and exposure days 5 to 8, whereas there was no change from exposure days 3 to 5. In addition, 7 d exposure to 0.8 mg/L AgNPs resulted in significant heart beat retardation in medaka embryos. AgNPs also caused a dose-dependent decrease in the hatching rate and body length of larvae. These results indicate that AgNP exposure causes severe developmental toxicity to medaka embryos and that toxicity levels are enhanced at certain developmental stages, which should be taken into consideration in assessments of metallic NPs toxicity to embryos.